1999
DOI: 10.1093/humrep/14.11.2844
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of the proliferation index, oestrogen receptors and progesterone receptors A and B in leiomyomata and normal myometrium during the menstrual cycle and under gonadotrophin-releasing hormone agonist therapy

Abstract: The cell proliferation-associated antigen Ki 67 and the immunohistochemical content of oestrogen receptors (ER), progesterone receptors AB (PRAB) and progesterone receptors B (PRB) were evaluated in leiomyomata and adjacent myometrium during the menstrual cycle and in leiomyomata under gonadotrophin-releasing hormone agonist (GnRHa) therapy. The proliferative status of muscular cells was measured by evaluating the percentage of nuclei staining positive for Ki 67 (proliferation index). Quantitative analysis (QH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
1
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 35 publications
12
92
1
12
Order By: Relevance
“…Stained TMA slides were graded jointly by two pathologists (RF, CB). A modified visual semiquantification method was used as previously described, 24 using a two-score system for immunointensity (II) and immunopositivity (IP). II and IP scores were summated.…”
Section: Immunohistochemical Stains and Statistical Analysismentioning
confidence: 99%
“…Stained TMA slides were graded jointly by two pathologists (RF, CB). A modified visual semiquantification method was used as previously described, 24 using a two-score system for immunointensity (II) and immunopositivity (IP). II and IP scores were summated.…”
Section: Immunohistochemical Stains and Statistical Analysismentioning
confidence: 99%
“…Compared with the surrounding endometrium, uterine myoma has a high concentration of progesterone receptors [8,9]. Mifepristone, onapristone, and ZK 230211 are pure progesterone receptor modulators.…”
Section: Progesterone Receptor Modulatorsmentioning
confidence: 99%
“…Because the tumors are hormonally dependent, develop during the reproductive period, and are suppressed by menopause, current medical treatments involve mainly hormonal manipulations [7]. Studies have shown the presence of estrogen and progesterone receptors with higher concentrations in myomas than in the surrounding endometrium [8,9]. Progesterone seems to have a dual effect on myomas by altering local growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…Mitotic activity is maximal during the luteal phase [59]. Several studies have shown an up-regulation of PR in uterine leiomyomata compared with normal adjacent myometrium at mRNA and protein levels [60].…”
Section: Treatment Of Uterine Leiomyomatamentioning
confidence: 99%
“…During the luteal phase, in the primate uterus, progesterone inhibits estrogen induced mitotic activity in the functional zones of the endometrial epithelium but shows some stimulatory effect on both the basalis and endometrial angiogenesis [7]. Progesterone can also play a key role on growth of benign smooth muscles tumours from uterine myometrium [8][9][10]. In normal breast epithelial cells, progesterone has important mitogenic properties with a peak of a mitotic activity during the luteal phase [11].…”
Section: Introductionmentioning
confidence: 99%